Manipulation of the Duration of the Initial Self-Control Task Within the Sequential-Task Paradigm: Effect on Exercise Performance - Boat, Ruth; Hunte, Raymon; Welsh, Emily; Dunn, Anna; Treadwell, Ellen; Cooper, Simon B. (Frontiers in Neuroscience, 2020)
Self-control exertion on an initial task has been associated with impaired performance on subsequent physical tasks also requiring self-control; an effect suggested to be mediated by changes in perceptions of pain and motivation. However, the effects of spending longer on the initial self-control task are unknown. This study, therefore, explored the potential for the duration of the initial self-control task to influence subsequent physical performance, perceptions of pain, and perceived motivation; particularly during the early stages of the physical task. In a within-subject design, 29 participants (11 male, 18 female) completed a wall-sit task until volitional exhaustion, on four separate occasions. Prior to each wall-sit, participants completed either a non-self-control task (congruent Stroop task) for 4 min, or a self-control task (incongruent Stroop task) for 4 (short duration), 8 (medium duration), or 16 (long duration) min. Participant’s perceptions of pain and motivation were recorded every 30 s during the wall-sit. Wall-sit performance time was analyzed using one-way ANOVA and perceptions of pain and motivation analyzed using multi-level modeling. Wall-sit performance time was significantly longer on the non-self-control exertion trial compared to all other trials (all p < 0.01), as well as longer on both the short duration and medium duration self-control exertion trials compared to the long duration self-control exertion trial (both p < 0.001). Perceptions of initial (at 30 s) pain and motivation were different between the trials (main effect of trial: pain, p = 0.001; motivation, p < 0.001); whereby longer durations of self-control exertion increased perceptions of pain and decreased motivation. The decrease in motivation during the wall-sit task was greater on the long duration self-control exertion trial compared to all other trials (trial∗time interactions, all p < 0.05). The present study provides novel evidence that spending longer on the initial self-control task led to greater detrimental effects on subsequent wall-sit performance time. Furthermore, longer duration self-control exertion tasks led to increased perceptions of pain and decreased motivation within the first 30 s of the wall-sit task, as well as a greater decrease in motivation across the wall-sit task. These attentional and motivational shifts may explain performance decrements following the exertion of self-control.